Madame Web [videorecording (DVD)] - Clarkson, S. J.; Sazama, Matt; Sharpless, Burk; Parker, Claire; Sanga, Kerem; Söderqvist, Johan, 1966-; Johnson, Dakota, 1989-; Sweeney, Sydney, 1997-; Merced, Isabela, 2001-; O'Connor, Celeste, 1998-; Rahim, Tahar, 1981-; Epps, Mike; et al. (Sony Pictures Home Entertainment, 2024)
After a near-fatal accident in the line of duty, Cassandra Webb -- a New York City paramedic -- starts to show signs of clairvoyance. Through her visions and a journey of self-discovery, she is forced to confront revelations about her past and how it is connected to a specific spider, and learns she must protect three young women from a mysterious adversary who wants them dead.